Meesterschap in tweevoud Novellen en schetsen van Rosalie en Virginie Loveling - Musschoot, Anne Marie (De Amazone-reeks, 2009)
Culture and history; Women: historical, geographic, persons treatment; Dutch literature; Dutch and Flemish literature